Reducing prolonged sedentary time using a treadmill desk acutely improves cardiometabolic risk markers in male and female adults. Issue 21 (2nd November 2018) - Champion, Rachael B; Smith, Lindsey R; Smith, Jennifer; Hirlav, Bogdana; Maylor, Benjamin D; White, Stephanie L; Bailey, Daniel P
ABSTRACT: This study evaluated the acute effects of interrupting prolonged sitting with an accumulated 2 h of light-intensity walking on postprandial cardiometabolic risk markers. In this randomised crossover trial, 24 participants (twelve males) aged 18–55 years took part in two, 6.5 h conditions: 1) prolonged sitting (SIT) and 2) sitting interrupted hourly with 20 min light-intensity treadmill desk walking at between 1.2–3.5 km/h −1 (INT-SIT). Standardized meals were provided at 0 h and 3 h. Blood samples and blood pressure measures were taken hourly. Statistical analyses were completed using linear mixed models. Postprandial incremental area under the curve responses (mmol/L∙6.5 h) for glucose (4.52 [3.47, 5.56] and 6.66 [5.62, 7.71] for INT-SIT and SIT, respectively) and triglycerides (1.96 [0.96, 2.96] and 2.71 [1.70, 3.71] for INT-SIT and SIT, respectively) were significantly lower in INT-SIT than SIT. Mean systolic and diastolic blood pressure responses were lower by 3% and 4%, respectively, in INT-SIT than SIT (P < 0.05). There was no significant condition x sex interaction effect for any outcomes (P > 0.05). These findings suggest that interrupting sitting with an accumulated 2 h of light-intensity walking acutely improves cardiometabolic risk levels in males and females compared with prolonged sitting.